Investment cash flow sensitivity under managerial optimism: New evidence from NYSE panel data firms - Mohamed, Ezzeddine Ben (2014)
Investment cash flow sensitivity constitutes one important block of the corporate financial literature. While it is well documented in standard corporate finance, it is still young under behavioral corporate finance. In this paper, we test the investment cash flow sensitivity among panel data of American industrial firms during 1999-2010. Using Q-model of investment (Tobin, 1969), we construct and introduce a proxy of managerial optimism following Malmendier and Tate (2005a) to show the impact of CEOs’ optimism in the relationship between investment and internal cash flow. Our results report a positive and significant coefficient of investment to cash flow for the full sample. While, on estimations of our model using sub-sample of more and less constrained firms, we find that the sensitivity exists stronger only for totally constrained group. We find also that board characteristics can reduce investment policy's distortions.